2020
DOI: 10.1038/s41598-020-71815-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different agronomic practices on the selective soil properties and nitrogen leaching of black soil in Northeast China

Abstract: Considering the large amount and high frequency application of concentrated fertilizer nitrogen in the Black Soil Region of Northeast China, the current laboratory/field simulation study aimed to explore the pollution risk of added nitrogen in black soil to groundwater and identify effective measures to prevent and control soil nitrogen leaching with an undisturbed soil column. The results showed that the saturated nitrogen adsorption capacities increased by 1.7%, 7.7% and 18.5% in ploughing, impervious agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
1
2
0
1
Order By: Relevance
“…As reported by Wang (2020) [ 41 ], the lower the BD value, the greater the water permeability; this indicates better conditions for plant root development and bacterial growth. The analysis of the values obtained in the experiment ( Figure 2 ) revealed an increase in BD with depth in both soils, which is a normal phenomenon.…”
Section: Resultssupporting
confidence: 57%
“…As reported by Wang (2020) [ 41 ], the lower the BD value, the greater the water permeability; this indicates better conditions for plant root development and bacterial growth. The analysis of the values obtained in the experiment ( Figure 2 ) revealed an increase in BD with depth in both soils, which is a normal phenomenon.…”
Section: Resultssupporting
confidence: 57%
“…Polymeric modifiers in PAA may also improve their strength properties. 7 Moreover, the cross-linked PAA has high water absorption capacity. PAA has excellent optical properties and non-weatherability.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 45 ] suggested that soil texture affects water infiltration and nutrient leaching losses, while Frick et al [ 22 ] concluded that N leaching losses in loamy sand/silt soil are more severe than in clay loamy soil, due to the lower retention rate and higher conductivity [ 46 ]. In addition, NH 4 + is readily adsorbed by internal clay surfaces [ 47 ], and soil containing 36.0–40.3 % clay minerals was found to adsorb 50–300 mg N kg −1 in the form of NH 4 + [ 48 ].…”
Section: Discussionmentioning
confidence: 99%